﻿Effects of Rooting Substrates on In Vitro Rooting of Anthurium andraeanum L. cv. Avanti - KEATMETHA, Wararat; SUKSA-ARD, Padungsak (Walailak Journal of Science and Technology (WJST), 2011)
A study was made of the effects of rooting substrates on in vitro rooting of Anthurium andraeanum L. cv. Avanti, orange flower. Initiation of root was attempted in several rooting substrates with modified ½ MS medium supplemented with 30 g/l sucrose. The cut end of the shoot was dipped in 2.5 g/l indole-3-butyric acid (IBA) before insertion in substrates. After 4 weeks of culture, it was found that roots were markedly induced in 8 and 12 g/l agar with 86.67 and 73.33% in root induction rate, 14.62 and 12.41 mm in root length, with 3.54 and 3.91 roots in root number respectively. However, 93.33% of root induction rate with 3.00 roots, and 11.66 mm in root length were produced on medium containing 1.5 g/l phytagel while peat moss and vermiculite could induce rooting at 46.67% with 7.86 and 6.66 mm in length, with 1.00 and 1.86 roots respectively. Root could not be induced in sphagnum moss. Anatomical study of root showed no abnormality in all rooting substrates. The roots formed in high concentrations of agar at 12 and 16 g/l, 2.0 and 2.5 g/l phytagel, and peat moss were thicker than those formed in other rooting substrates. Especially, root formed in peat moss had the largest vascular diameter. However, roots formed in phytagel, peat moss, and vermiculite had more root hairs than those formed in agar substrate. Plantlets, rooted in peat moss and vermiculite, survived at 100% after acclimation in a mixture of soil and coconut husk.